PEMANFAATAN SISTEM PENDUKUNG KEPUTUSAN BAGI SISWA/I LKP BINTANG MULIA BATUBARA - Dahriansah Dahriansah; Maulana Dwi Sena; Ruri Azhari Dalimunthe (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2023)
Abstract: LKP Bintang Mulia Batubara is an institution engaged in the field of education, especially in the field of computers. In general, Bintang Mulia Coal LKP students only study office applications such as Ms Office so that students' knowledge of computer technology is still limited. In accordance with technological developments there is still much that is not known by LKP Bintang Mulia students, one of which is the Decision Support System. The benefit of implementing a decision support system is to increase the ability of decision makers by providing better decision alternatives so that they can help to make decisions such as selecting the best student, so that an objective assessment is obtained. The purpose of this activity is to broaden students' insights so that they know the role of the system decision support. The results obtained from this dedication are that students know that there are many things that can be done by implementing a decision support system such as selecting outstanding students, choosing learning methods that students like.Keywords: education; computer; decision support systemAbstrak: LKP Bintang Mulia Batubara adalah Lembaga yang bergerak di bidang Pendidikan, khususnya dibidang komputer. Pada umumnya siswa LKP bintang mulia batubara hanya mempelajari aplikasi perkantoran seperti Ms Office sehingga pengetahuan siswa/I mengenai teknologi komputer masih terbatas. Sesuai dengan perkembangan teknologi masih banyak yang belum diketahui oleh siswa LKP Bintang Mulia , salah satunya adalah Sistem Pendukung Keputusan. Manfaat dari penerapan sistem pendukung keputusan adalah untukmeningkatkan kemampuan pengambil keputusan dengan memberikan alternatif keputusan yang lebih baik sehingga dapat membantu untuk menetapkan sebuah keputusan seperti pemilihan siswa terbaik, sehingga didapat penilaian yang objektif.Tujuan dari kegiatan ini adalah untuk menambah wawasan siswa agar mengenal peran sistem pendukung keputusan. Hasil yang didapat dari pengabdian ini adalah para siswa mengetahui bahwa banyak hal yang dapat dilakukan dengan menerapkan sistem pendukung keputusan seperti pemilihan siswa berprestasi, pemilihan metode pembelajaran yang disukai para siswa.Kata kunci: pendidikan; komputer; SPK